2019
DOI: 10.26550/2209-1092.1044
|View full text |Cite
|
Sign up to set email alerts
|

Australian perioperative nurses’ attitudes, levels of knowledge, education and support needs related to organ donation and procurement surgery: A national survey

Abstract: Australian perioperative nurses' attitudes, levels of knowledge, education and Australian perioperative nurses' attitudes, levels of knowledge, education and support needs related to organ donation and procurement surgery: A national support needs related to organ donation and procurement surgery: A national survey survey Cover Page Footnote Cover Page Footnote Acknowledgement The project was supported by ACORN who made their membership database available for the delivery of the link to the survey. A special t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Moreover, OR nurses may also feel overwhelmed and distressed during the procurement procedure due to other challenges such as being unfamiliar with procurement procedures and postmortem care (Smith et al, 2015a). This was echoed in a recent Australian survey conducted by Smith et al (2019), which found that over half of the participating nurses felt incompetent during organ procurement procedures.…”
Section: Organ Procurement Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, OR nurses may also feel overwhelmed and distressed during the procurement procedure due to other challenges such as being unfamiliar with procurement procedures and postmortem care (Smith et al, 2015a). This was echoed in a recent Australian survey conducted by Smith et al (2019), which found that over half of the participating nurses felt incompetent during organ procurement procedures.…”
Section: Organ Procurement Proceduresmentioning
confidence: 99%
“…This was echoed in a recent Australian survey conducted by Smith et al. (2019), which found that over half of the participating nurses felt incompetent during organ procurement procedures.…”
Section: Introductionmentioning
confidence: 96%